2022
DOI: 10.1055/a-1730-5251
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prediabetes and Osteoarthritis: A Meta-Analysis

Abstract: Some studies have suggested that diabetes may be a risk factor for osteoarthritis. However, whether prediabetes is also associated with osteoarthritis has not been comprehensively examined. We performed a meta-analysis to evaluate the relationship between prediabetes and osteoarthritis. This meta-analysis included relevant observational studies from Medline, Embase, and Web of Science databases. A random-effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, after further controlling for other factors such as BMI, the association became insignificant [ 46 ]. A potential reason for this insignificant association is that DM can be categorized as either prediabetes or DM since previous meta-analysis found no association between prediabetes and OA, indicating that mild hyperglycemia might not be associated with an increased risk of OA [ 40 ]. Another possible explanation is the mediation effect of obesity on DM and OA as a shared risk factor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after further controlling for other factors such as BMI, the association became insignificant [ 46 ]. A potential reason for this insignificant association is that DM can be categorized as either prediabetes or DM since previous meta-analysis found no association between prediabetes and OA, indicating that mild hyperglycemia might not be associated with an increased risk of OA [ 40 ]. Another possible explanation is the mediation effect of obesity on DM and OA as a shared risk factor.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies included type 2 DM (T2DM) and specific joints such as knee and hand OA. Other narrative reviews have looked at the association between metabolic syndrome and OA [ 16 , 36 , 37 , 38 , 39 , 40 ]. Previous reviews were limited to specific joints for OA and specific forms of DM such as T2DM and did not investigate the impact of DM on symptoms and physical function among people with OA.…”
Section: Introductionmentioning
confidence: 99%
“…First, knee OA and cardiovascular diseases have common risk factors such as age and obesity. Moreover, knee OA can increase the risk of traditional risk factors for cardiovascular diseases, i.e., hypercholesterolemia [29], hypertension [30], aortic calcification [31], lumbar atherosclerotic calcification [32] or diabetes [33,34]. Of importance, a study with a 3 year follow-up reported a strong association between hypertension and impaired glucose tolerance with knee OA occurrence [35].…”
Section: Discussionmentioning
confidence: 99%